Manajemen Remaja Masjid Nurul Ittifaq dalam Melaksanakan Kegiatan Keagamaan di Desa Pontang Kecamatan Ambulu - Fitri, Tia Amelia (Fakultas Dakwah UIN KHAS Jember, 2023)
The Youth of the Nurul Ittifaq Mosque in Pontang Village is a youth association related to the mosque, therefore it is necessary to introduce a work program that is oriented towards youth and mosque development. Research objective: To determine the management of Nurul Ittifaq Mosque Youth in Carrying out Religious Activities in Pontang Village, Ambulu District, supporting and inhibiting factors faced by Nurul Ittifaq Mosque Teenagers in Carrying out Religious Activities in Pontang Village, Ambulu District. Research Results: The form of management of religious activities carried out is: First, planning for Remas Nurul ittifaq, namely so that the activities to be carried out can run according to plan. Second, organizing is important because it makes it easier to establish communication between members, committees and administrators. Third, the Nurul Ittifaq Mosque Youth mobilizes each coordinator under them through coordination with members. Fourth, the importance of monitoring Remas Nurul Ittifaq's activities is so that they run according to the vision, mission and goals. The supporting factors obtained are in carrying out religious activities, namely having full support from the mosque management and having sufficient financial resources to carry out activities that come from donors, the enthusiasm of the members. The obstacle factor that occurs is the lack of self-awareness of each administrator and member. mosque youth in carrying out programmed religious activities as well as economic factors.